Convergence of Low‐Fertility Policies Beyond Policy Transfer: A Comparative Analysis of Korea and Hungary - Kilkon Ko; M. Jin Lee; Tamás Pesuth (Public Administration and Development, 2026)
ABSTRACT This study compares policy responses to persistent low fertility in Korea and Hungary, two countries facing similar demographic pressures but embedded in distinct institutional settings. It asks whether the diffusion of pronatalist policies has produced convergence in the design, implementation, and effects of fertility policy in these cases. Drawing on comparative institutional analysis and recent policy and demographic data, the study shows that although both countries have adopted similar instruments—including cash transfers, housing support, and parental leave—their policy frameworks differ substantially in governance, targeting, and political justification. Korea's approach is fragmented, technocratic, and broadly inclusive, whereas Hungary's is centralized, ideologically framed, and more selective in its targeting. The findings suggest that similar policy instruments do not necessarily generate similar demographic or social outcomes: Korea has remained at ultra‐low fertility with limited evidence of behavioral response, while Hungary experienced a modest and temporary increase in fertility alongside heightened political salience. These findings challenge the assumption that benchmarking similar policy instruments ensures substantive convergence in outcomes. This study refines policy convergence theory by distinguishing instrumental similarity from deeper divergence in institutional logic, governance, and implementation intensity.